2019
DOI: 10.17240/aibuefd.2019.19.43815-446550
|View full text |Cite
|
Sign up to set email alerts
|

İlköğreti̇m Matemati̇k Öğretmen Adaylarinin Hafiza Oyunlari İle Hafiza Oyunlarinin Matemati̇k Öğreti̇mi̇ne Katkisina İli̇şki̇n Görüşleri̇

Abstract: Bu makalenin amacı, ilköğretim matematik öğretmen adaylarının zekâ oyunu türlerinden hafıza oyunları ve hafıza oyunlarının matematik öğretimine katkısı hakkındaki düşüncelerini incelemektir. Bu amaçla, 2017-2018 öğretim yılında Ankara ilindeki bir devlet üniversitesinde Matematik Eğitimi Anabilim Dalı İlköğretim Matematik Öğretmenliği Programına devam eden toplam 39 öğretmen adayının görüşüne başvurulmuştur. İlköğretim matematik öğretmen adaylarının hafıza oyunları ile ilgili görüşleri, araştırmacılar tarafınd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…This situation is in line with the finding that Akkaya et al (2022) analyzed the mind games in terms of primary school mathematics lesson objectives, and found that 32 board games mostly matched with the objectives in the learning areas of numbers and operations and geometry. In the literature, when routine problems in mathematics lessons are compared with the use of mind games, it is emphasized that mind games improve students' problem solving, communication and reasoning skills (Saygı & Alkaş Ulusoy, 2019;Taş & Yöndemli, 2018;Yılmaz, 2019). In addition to the results mentioned in the literature, it is thought that the fact that the mind games played in the lessons are related to the mathematics lesson objectives in line with the results of this research supports the students' use of number sense strategies.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…This situation is in line with the finding that Akkaya et al (2022) analyzed the mind games in terms of primary school mathematics lesson objectives, and found that 32 board games mostly matched with the objectives in the learning areas of numbers and operations and geometry. In the literature, when routine problems in mathematics lessons are compared with the use of mind games, it is emphasized that mind games improve students' problem solving, communication and reasoning skills (Saygı & Alkaş Ulusoy, 2019;Taş & Yöndemli, 2018;Yılmaz, 2019). In addition to the results mentioned in the literature, it is thought that the fact that the mind games played in the lessons are related to the mathematics lesson objectives in line with the results of this research supports the students' use of number sense strategies.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Literatürde oyunla matematik öğretimini ele alan birçok çalışma yer almaktadır. Bu çalışmalardan bazıları oyunlarla matematik öğretiminin erişiye (Başün ve Doğan, 2020;Beyhan ve Tural, 2007;Biriktir, 2008;Tural, 2005) veya tutuma (Çankaya ve Karamete, 2008;Tural, 2005) olan etkisini ele alırken, bazıları oyunlara dair öğrenci (Başün ve Doğan, 2017;Şahin, 2016), öğretmen (Doğan ve Sönmez, 2019;Gürbüz, Gülburnu ve Şahin, 2017;Özata ve Çoşkuntuncel, 2019), öğrenci-öğretmen (Duran ve Kaplan, 2014) veya öğretmen adaylarının (Saygı ve Alkaş Ulusoy, 2019;Topçu, Küçük ve Göktaş, 2014;Usta vd., 2017;Yıldız Durak ve Karaoğlan Yılmaz, 2019) görüşlerini incelemiştir. Birçok çalışmada oyunların öğretimde etkili olduğu her ne kadar sıklıkla dile getirilse de, öğretim ortamlarına entegre edilen oyun örnekleri nispeten azdır (Linehan, Kirman, Lawson ve Chan, 2011).…”
Section: Introductionunclassified